Productos y atractivos turísticos del cantón Latacunga, parroquias 11 de Noviembre y Poalo. - Osorio Yugse, Cristian Paul (2023)
This research work was carried out in the 11 de Noviembre and Poaló parishes belonging to the Latacunga canton, where its main problem is the dissemination and marketing of products and tourist attractions, 3 key objectives were developed to help the creation of strategies which serve as a contribution to tourism in the Latacunga canton. In the process of the investigation, the update of information about the tourist attractions was carried out, with the support of the inventory of the year 2015, where a review of the tourist attractions that each parish of the Latacunga canton has, field trips were carried out, with a focus qualitative to be able to demonstrate the general characteristics of each one of the tourist attractions, and as a support guide to fill out the sheets offered by the Ministry of Tourism (MINTUR) methodology, with the gathering of information and the completion of the sheets it was possible to Evidence that in the 11 de Noviembre parish there are 10 tourist attractions, 1 natural, 9 cultural, 2 cultural attractions are new to be included in the inventory of tourist attractions in the Latacunga canton, and in the Poaló parish 6 natural and 11 cultural attractions, Most of the attractions over the years have improved in terms of services, infrastructure, accessibility, activities, obtaining the progress of hierarchies. For the second objective, the Prom Peru tourist products manual was used, which contains important information for the collection of information, a descriptive approach was used that helped to obtain all the details contained in this case, the existence of the tourist route named Poaló - Mr. de Maca, a questionnaire is developed for an interview addressed to the tourism analyst of the Latacunga canton Juan Pablo Parreño concluding with the generation of the database, which consists of information on tourist attractions; Tilipulo Farm, Poaló Church, Sanctuary of the Lord of Maca Chico, Gastronomy of Poaló, Handicrafts of Fajas and Shigras, the Poncho Looms, tourist services; accommodation, food, transportation and activities such as; photography, walking, cycling, purchase of handicrafts and gastronomy tasting. Finally, in the third objective, the dissemination and marketing strategies of the product and tourist attractions of the 11 de Noviembre and Poaló parishes are carried out, as such, a Focus group was developed virtually with people from the different parishes, a SWOT analysis where it consists of of Strengths, Opportunities, Weaknesses and Threats and matrices such as MEFE. MEFI, which values the external and internal factors of the investigation and the crossed SWOT, analyzing these matrices, viable strategies were developed to be able to apply them in the dissemination and tourist marketing, an action plan as a proposal in case of being applied.